2022
DOI: 10.31486/toj.21.0057
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations in COVID-19–Positive African American Patients

Abstract: Background: The United States of America is the leading country in confirmed cases of and deaths from severe acute respiratory syndrome coronavirus 2, the virus that causes coronavirus disease 2019 (COVID-19). In April and May 2020, respectively, 0.2% of patients in a Chinese COVID-19–positive cohort and 20.4% of patients in an Italian COVID-19–positive cohort developed cutaneous abnormalities. Cutaneous abnormalities associated with COVID-19 are not well documented or discussed, and investigation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…3,20 Sachdeva et al conducted a review of the literature on 72 COVID-19-related cutaneous manifestations and found that 12.5% of patients presented with cutaneous lesions prior to the onset of symptoms. 21 As a result, the occurrence of COVID-19-related cutaneous manifestations has steadily increased, paralleling the global spread of SARS-CoV-2. This could be explained by a variant of concerns (VOCs), as one study found that cutaneous manifestations were significantly more common in the Delta wave than in the Omicron wave.…”
Section: Epidemiologic Characteristics Of Covid-19 Cutaneous Manifest...mentioning
confidence: 99%
See 4 more Smart Citations
“…3,20 Sachdeva et al conducted a review of the literature on 72 COVID-19-related cutaneous manifestations and found that 12.5% of patients presented with cutaneous lesions prior to the onset of symptoms. 21 As a result, the occurrence of COVID-19-related cutaneous manifestations has steadily increased, paralleling the global spread of SARS-CoV-2. This could be explained by a variant of concerns (VOCs), as one study found that cutaneous manifestations were significantly more common in the Delta wave than in the Omicron wave.…”
Section: Epidemiologic Characteristics Of Covid-19 Cutaneous Manifest...mentioning
confidence: 99%
“…21,35,36 The immune response to infection also activates Langerhans cells, resulting in vasodilation and spongiosis. 21,35,36 The presence of ACE2, the primary receptor for SARS-CoV-2 entering skin cells, may explain some of the vascular skin lesions associated with COVID-19 infection due to a significant immune antiviral response. 37,38 Maculopapular eruptions may be caused by SARS-CoV-2 particles and immune complex deposition that damage dermal vessels and cause lymphocytic vasculitis.…”
Section: Pathophysiology Of Covid-19 On Cutaneous Manifestationsmentioning
confidence: 99%
See 3 more Smart Citations